THE EFFECTIVENESS OF THE PARKING BAN POLICY IN SUKABUMI CITY BY THE SUKABUMI CITY TRANSPORTATION DEPARTMENT - Fauzy, Muhammad Rizki; Nur, Tuah; Purwanti, Dian (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
The effectiveness of the parking ban policy in Sukabumi City implemented by the Transportation Department has been regulated by the Undang-Undang Republik Indonesia Nomor 22 Tahun 2009 concerning Road Traffic and Transportation. This research is motivated by the presence of illegal parking at several points such as Jalan R.E Martadinata, Jalan Gudang Kebonjati, Jalan Kramat, and Jalan A. Yani. This research aims to see the effectiveness of the parking ban policy implemented by the Sukabumi City Transportation Agency. This research uses Duncan's theory of effectiveness with three dimensions, namely goal achievement, Integrity, and Adaptation. This research method uses a descriptive qualitative approach with interview, observation, and documentation techniques. The results of this study show that it is quite good but in its implementation, there are still many motorists who do not realize the importance of orderly traffic or obey the rules set by the Sukabumi City Transportation Office.